Non-traditional producers of microbial exopolysaccharides - Pirog, Tatiana; Voronenko, Andryi; Ivahniuk, Mykola (My University, 2018)
Data on exopolysaccharides synthesis by psychrophilic fungi and bacteriae, halo- and thermophilic archaea and bacteriae, including those isolated from deep-sea hydrothermal vents − sources − were provided. Physiologic significance, physico-chemical properties and possible practical applications of exopolysaccharides from unusual sources were analyzed. Most of them have immunomodulating, antiviral, anticoagulant, antitumor, antioxidant activities promising for medical and pharmaceutical applications. Meanwhile, based on the literature date, the conclusion follows about the urgent necessity to develop efficient technologies for synthesis of these exopolysaccharides by nontraditional producers, which currently lags far behind common techniques. Наведено дані про синтез екзополісахаридів психрофільними грибами та бактеріями, гало- та термофільними археями та бактеріями, у тому числі виділеними з глибоководних гідротерм – джерел. Було проаналізовано фізіологічне значення, фізико-хімічні властивості та можливі практичні застосування екзополісахаридів з незвичайних джерел. Більшість із них мають імуномодулюючу, противірусну, антикоагулянтну, протипухлинну, антиоксидантну активність, перспективну для застосування в медицині та фармацевтиці. Водночас, виходячи з літературних даних, випливає висновок про нагальну необхідність розробки ефективних технологій синтезу цих екзополісахаридів нетрадиційними продуцентами, які на сьогодні значно відстають від загальноприйнятих.
Keywords: екзополісахариди; термофіли; психрофіли; галофіли; гідротермальні венти; кафедра біотехнології і мікробіології; exopolysaccharides; thermophiles; psychrophiles; halophiles; hydrothermal vents